2021
DOI: 10.1038/s41598-021-90475-1
|View full text |Cite
|
Sign up to set email alerts
|

Poor performance of open incisional biopsy for the microbiological diagnosis of periprosthetic knee joint infection

Abstract: The accurate preoperative diagnosis of periprosthetic joint infection (PJI) of total knee arthroplasty (TKA) can be difficult despite the use of a combination of serum and synovial markers. In such inconclusive cases, incisional open biopsy might be considered. This study investigates the usefulness of biopsies in patients with inconclusive diagnostic findings. We retrospectively identified 63 patients who underwent incisional biopsy for chronic PJI in the operation theatre following TKA revision between 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…In our cohort, we observed unexpected positive cultures in 7.89% of the patients, of which one patient needed additional revision surgeries due to persisting PJI. That rate was lower when compared to data of previous authors who found unexpected positive cultures in 23% of all cases [ 33 ]. Revision surgeries related to unexpected cultures were not reported by the authors.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…In our cohort, we observed unexpected positive cultures in 7.89% of the patients, of which one patient needed additional revision surgeries due to persisting PJI. That rate was lower when compared to data of previous authors who found unexpected positive cultures in 23% of all cases [ 33 ]. Revision surgeries related to unexpected cultures were not reported by the authors.…”
Section: Discussioncontrasting
confidence: 78%
“…A recent meta-analysis concluded that OIB is not superior to synovial fluid aspirations alone but contributes to the already existing diagnostic algorithms and improves diagnostic accuracy [ 34 ]. Since that analysis, few authors published results concerning the usage of OIB for the diagnosis of PJI [ 32 , 33 ]. Klaber et al assessed OIB as a diagnostic tool following two culture-negative aspirations in suspected PJI in THA and TKA [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations